1978
DOI: 10.1128/aac.13.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Azlocillin and Mezlocillin Against Gram-Negative Organisms: Comparison with Other Penicillins

Abstract: The activities of azlocillin and mezlocillin were compared with those of carbenicillin, ticarcillin, and pirbenicillin against a wide range of gram-negative organisms. The tyvo new drugs were considerably more active than carbenicillin against Klebsiella species and Escherichia coli. Carbenicillin was twice as active against Proteus mirabilis as mezlocillin and four times as active as azlocillin. Against Pseudomonas aeruginosa, azlocillin was eight times as active as carbenicillin. Azlocillin and mezlocillin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
2
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 10 publications
1
15
2
1
Order By: Relevance
“…The MICs and MBCs of these agents for 20 strains of P. aeruginosa, the mean serum levels after intravenous infusion of 5 g of these drugs, and the inhibitory and bactericidal activities of serum obtained 1 and 6 h after onset of the infusion were similar. These findings are in accordance with those reported by others (5,8,9,12) who found a similar in vitro activity of mezlocillin and ticarcillin against P. aeruginosa; the concentration of mezlocillin that inhibited 75% of strains studied by others was quite similar to our findings. We also found a twofold difference between the MICs and MBCs of mezlocillin.…”
Section: Discussionsupporting
confidence: 94%
“…The MICs and MBCs of these agents for 20 strains of P. aeruginosa, the mean serum levels after intravenous infusion of 5 g of these drugs, and the inhibitory and bactericidal activities of serum obtained 1 and 6 h after onset of the infusion were similar. These findings are in accordance with those reported by others (5,8,9,12) who found a similar in vitro activity of mezlocillin and ticarcillin against P. aeruginosa; the concentration of mezlocillin that inhibited 75% of strains studied by others was quite similar to our findings. We also found a twofold difference between the MICs and MBCs of mezlocillin.…”
Section: Discussionsupporting
confidence: 94%
“…HR 756 was also more active than the recent cephalosporins, cefuroxiime (2,5), cefoxitin (3), and cefamandole (2). In addition HR 756 has modest activity against P. aeruginosa, comparable to the a-amino-substituted penicillin mezlocillin (1,9). Other pathogens, often consid- Passage of a variety of strains on media containing HR 756 indicated that resistance could readily be induced in vitro and that this resistance was stable on serial transfer on antibioticfree media.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown this antibiotic to have a spectrum of activity encompassing that of the cephalosporins and penicillins, including activity against Escherichia coli, species of the Klebsiella-Enterobacter-Serratia group, Proteus, Pseudomonas, Haemophilus influenzae, and Neisseria gonorrhoea (3,16). It is more active than ampicillin, carbenicillin, and cephalothin against some gram-negative bacilli (17). It is also active against Streptococcus faecalis and other gram-positive bacteria which do not produce , 8-lactamase.…”
mentioning
confidence: 99%